2016
DOI: 10.1016/j.csi.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The strengths and weaknesses of software architecture design in the RUP, MSF, MBASE and RUP-SOA methodologies: A conceptual review

Abstract: The importance of Software Architecture design has been acknowledged as a very important factor for a high-quality software development. Different efforts in both industry and academia have produced multiple system development methodologies (SDMs) that include SA design activities. In addition, standardization bodies have defined different recommendations regarding Software Architecture design. However, in industry Software Architecture best practices are currently poorly employed. This fact constrains the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Toda et al [5] deeply analyzed SOA software engineering development technology and proposed that the introduction of object-oriented software such as component in the development and design of distributed management system could improve system rapidity and reliability and then promote system development efficiency and expansibility. Reyes-Delgado et al [6] analyzed the adherence degree of four main recognized SDMs and RUP (Rational Unified Process), MSF (Microsoft Solutions Framework), MBASE (Model-Based System Architecting and Software Engineering), and RUP-SOA (Rational Unified Process for Service-oriented Architecture) to the best practices of Software Architecture design, and the good application effect was gained.…”
Section: State Of the Artmentioning
confidence: 99%
“…Toda et al [5] deeply analyzed SOA software engineering development technology and proposed that the introduction of object-oriented software such as component in the development and design of distributed management system could improve system rapidity and reliability and then promote system development efficiency and expansibility. Reyes-Delgado et al [6] analyzed the adherence degree of four main recognized SDMs and RUP (Rational Unified Process), MSF (Microsoft Solutions Framework), MBASE (Model-Based System Architecting and Software Engineering), and RUP-SOA (Rational Unified Process for Service-oriented Architecture) to the best practices of Software Architecture design, and the good application effect was gained.…”
Section: State Of the Artmentioning
confidence: 99%
“…However, in a world of agile engineering approaches, where incremental solutions are provided step-by-step in close collaboration with the users, and in our context, the platform providers, such a setting is not possible. This is also the reason why, although such empirical research is demanded in recent literature [8], no results are reported. Furthermore, the question is raised as to whether there is a need at all for a single method for the Internet of Things [21].…”
Section: Discussionmentioning
confidence: 96%
“…Typically, SOAD methodologies support the break-down from use cases to the specification of service requirements according to the constraints of service ecosystems. More recent comparison studies of software engineering methodologies were carried out, such as in Reference [8]. However, on the one hand, they all stayed on the conceptual level, and on the other hand, they all just focused on the top-down approach and ignored or at least neglected the fact that there may be already existing capabilities which may match the requirements.…”
Section: Related Workmentioning
confidence: 99%
“…Services computing and cloud computing are two mainly co‐existing paradigms that are widely demanded at present software systems . The services computing paradigm aims at the development of medium‐sized and large distributed inter‐organizational systems by assembling it as a system of service providers and consumers, known as a service‐oriented computing application .…”
Section: Introductionmentioning
confidence: 99%